The Potential Role of RP105 in Regulation of Inflammation and Osteoclastogenesis During Inflammatory Diseases - Fan, Zhou; Pathak, Janak L.; Ge, Linhu (Frontiers in Cell and Developmental Biology, 2021)
Inflammatory diseases have a negative impact on bone homeostasis via exacerbated local and systemic inflammation. Bone resorbing osteoclasts are mainly derived from hematopoietic precursors and bone marrow monocytes. Induced osteoclastogenesis during inflammation, autoimmunity, metabolic diseases, and cancers is associated with bone loss and osteoporosis. Proinflammatory cytokines, pathogen-associated molecular patterns, or endogenous pathogenic factors induce osteoclastogenic differentiation by binding to the Toll-like receptor (TLR) family expressed on the surface of osteoclast precursors. As a non-canonical member of the TLRs, radioprotective 105 kDa (RP105 or CD180) and its ligand, myeloid differentiation protein 1 (MD1), are involved in several bone metabolic disorders. Reports from literature had demonstrated RP105 as an important activator of B cells, bone marrow monocytes, and macrophages, which regulates inflammatory cytokines release from immune cells. Reports from literature had shown the association between RP105 and other TLRs, and the downstream signaling mechanisms of RP105 with different “signaling-competent” partners in immune cells during different disease conditions. This review is focused to summarize: (1) the role of RP105 on immune cells’ function and inflammation regulation (2) the potential regulatory roles of RP105 in different disease-mediated osteoclast activation and the underlying mechanisms, and (3) the different “signaling-competent” partners of RP105 that regulates osteoclastogenesis.